Demokrasi Ideal di Benua Afrika: Tantangan dan Potensi - Ramadhan, Khusairi; Rahadian Surya , Mohammad (Jurnal Review Politik, 2018)
Many are hope that there would be a movement called Africa Springs, like the one in the Middle East which is called as Arab Springs. It is worth noting that eventhough Arab Springs is only succes in the Middle East and several African States; not all African states enjoys the spillover of it. The process to gain democracy trough Arab Springs was either by peace movement or violent. Weak on democracy, the tightening of press freedom, the strength of military authority, the influence of older generations who tend to be conservative in the wheel of government, inadequate access to technology, are a number of factors in the failure of Africa Spring. However, there are two states that could be beacons of democracy in Africa; Kenya and Zimbabwe. Moreover, one of the milestones in the success of a country's democracy is Political Security - although many countries ignore it. In this case, Kenya and Zimbabwe are examples of countries that have succeeded in implementing (almost) full democracy but still have many obstacles to achieving it. In addition, Africa Spring remains a very beautiful dream for millennial generations on the black continent.